Pengembangan media digital awareness line untuk mencegah bullying dan tawuran di lembaga pendidikan - Syarifah; Fauzi, Andika Putra Pratama; Yasmin, Noor Aini; Huaida, Siti Maria; Rahman, Imas Kania (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Based on data from the United Nations Children's Fund (UNICEF), 41% of 15-year-old students in Indonesia have experienced bullying more than a few times a month. Furthermore, the delinquency that is rampant among teenagers is brawls. As stated in the Central Statistics Agency (BPS) report, throughout 2021 there were 188 villages throughout Indonesia that became arenas for mass fights between students. This research aims to develop e-book media for preventing bullying and brawl behavior for junior high school students. The research method used is development research (Research and Development) with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. This e-Book has gone through feasibility testing with several stages including feasibility testing by 4 experts, 30 BKPI students, and 30 junior high school students. Furthermore, the e-book was tested on 103 Kosgoro Junior High School students in Bogor City. The results showed that this e-book Awareness Line media innovation had received a feasibility assessment from media experts and material experts. After being tested on Kosgoro Junior High School students, an average result of 99.36% was obtained, which shows that this e-book is quite effective in increasing student awareness in preventing bullying and brawling behavior. Abstrak Berdasarkan data yang dimiliki United Nations Children's Fund (UNICEF) bahwa 41% siswa berusia 15 tahun di Indonesia pernah mengalami bullying lebih dari beberapa kali dalam sebulan. Selanjutnya kenakalan yang marak dilakukan oleh kalangan remaja yaitu tawuran. Sebagaimana tercantum pada laporan Badan Pusat Statistik (BPS), sepanjang 2021 ada 188 desa/kelurahan di seluruh Indonesia yang menjadi arena perkelahian massal antar pelajar. Penelitian ini bertujuan untuk mengembangkan media e-book pencegahan perilaku bullying dan tawuran untuk siswa SMP. Metode penelitian yang digunakan adalah penelitian pengembangan (Research and Development) dengan model ADDIE, yang mencakup lima tahap: Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. E-Book ini telah melalui uji kelayakan dengan beberapa tahap diantaranya uji kelayakan oleh 4 ahli, 30 mahasiswa BKPI, dan 30 siswa SMP. Selanjutnya, e-book diujicobakan kepada 103 siswa SMP Kosgoro Kota Bogor. Hasil penelitian menunjukkan bahwa inovasi media e-book Awareness Line ini telah mendapatkan penilaian kelayakan dari ahli media dan ahli materi. Setelah diujicobakan kepada siswa SMP Kosgoro diperoleh hasil rata-rata sebesar 99,36% yang menunjukkan bahwa e-book ini cukup efektif dalam meningkatkan kesadaran siswa dalam mencegah perilaku bullying dan tawuran.